2022
DOI: 10.1093/oncolo/oyac112
|View full text |Cite
|
Sign up to set email alerts
|

Improving Adherence to Adjuvant Endocrine Therapy in Sub-Saharan Africa: Challenges and Innovative Nurse-Driven Solutions

Abstract: Despite its proven efficacy, adherence to adjuvant endocrine therapy remains a significant challenge around the world and in sub-Saharan Africa. This commentary discusses the results of the study by Getachew and colleagues, which examined the use of a multi-pronged nurse-led intervention to improve adherence to endocrine therapy in Ethiopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Recent reviews of global studies had identified several factors that are associated with non-adherence to AET. These factors include personal demographic factors; sideeffects and quality of life; knowledge of cancer, forgetfulness, beliefs, depressive symptoms and attitudes; socio-behavioral factors like selfefficacy (the belief in one's own capacity to achieve a health goal through behavior modification); and structural health-system factor (healthcare provider relationship) and social support (Fadelu et al, 2022).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Recent reviews of global studies had identified several factors that are associated with non-adherence to AET. These factors include personal demographic factors; sideeffects and quality of life; knowledge of cancer, forgetfulness, beliefs, depressive symptoms and attitudes; socio-behavioral factors like selfefficacy (the belief in one's own capacity to achieve a health goal through behavior modification); and structural health-system factor (healthcare provider relationship) and social support (Fadelu et al, 2022).…”
Section: Significance Of the Studymentioning
confidence: 99%